LncRNA Tuna is activated in cadmium-induced placental insufficiency and drives the NRF2-mediated oxidative stress response - Simmers, Mark D.; Jima, Dereje D.; Tsuji, Yoshiaki; Cowley, Michael (Frontiers in Cell and Developmental Biology, 2023)
Cadmium (Cd) is a toxic heavy metal found throughout the environment and one of the top ten toxicants of major public health concern identified by the World Health Organization. In utero Cd exposure causes fetal growth restriction, malformation, and spontaneous abortion; however, the mechanisms by which Cd impacts these outcomes are poorly understood. Cd accumulates in the placenta, suggesting that these negative outcomes may be a consequence of disrupted placental function and placental insufficiency. To understand the impact of Cd on gene expression within the placenta, we developed a mouse model of Cd-induced fetal growth restriction through maternal consumption of CdCl2 and performed RNA-seq on control and CdCl2 exposed placentae. The top differentially expressed transcript was the Tcl1 Upstream Neuron-Associated (Tuna) long non-coding RNA, which was upregulated over 25-fold in CdCl2 exposed placentae. Tuna has been shown to be critical for neural stem cell differentiation. However, within the placenta, there is no evidence that Tuna is normally expressed or functional at any developmental stage. To determine the spatial expression of Cd-activated Tuna within the placenta, we used in situ hybridization as well as placental layer-specific RNA isolation and analysis. Both methods confirmed the absence of Tuna expression in control samples and determined that Cd-induced Tuna expression is specific to the junctional zone. Since many lncRNAs regulate gene expression, we hypothesized that Tuna forms part of the mechanism of Cd-induced transcriptomic changes. To test this, we over-expressed Tuna in cultured choriocarcinoma cells and compared gene expression profiles to those of control and CdCl2 exposed cells. We demonstrate significant overlap between genes activated by Tuna overexpression and genes activated by CdCl2 exposure, with enrichment in the NRF2-mediated oxidative stress response. Herein we analyze the NRF2 pathway and show that Tuna increases NRF2/NRF2 both at the transcript and protein levels. Tuna drives increased NRF2 target gene expression, a result that is abrogated with the use of an NRF2 inhibitor, confirming that Tuna activates oxidative stress response genes through this pathway. This work identifies the lncRNA Tuna as a potential novel player in Cd-induced placental insufficiency.